Praxis democrática de los docentes en las instituciones educativas públicas de educación básica regular de Márquez - Callao - Morillo Flores, John Janel (2010)
The present research tries to describe, to analyze and to establish the level of democratic practice of the teachers in the Educational public Institutions of basic regular education of Márquez – Callao; it means, how the educators compromise themselves with the democracy in the educational institution where they work, considering that they are the principal forming agent and model of life for his pupils. The instrument was designed by the author, measured the democratic practice of a population of 54 teachers: their conscious and reflexive exercise of the values of the democracy (incorporation, participation, freedom, tolerance, equality, criticidad, responsibility and justice) described and defined in the theoretical frame. The instrument was applied to 22 teachers (40, 7 % of the population) and 188 pupils, (9, 4 % of the population) these think about the democratic practice of the first ones. After processing the information and have done credit the triangulation it is concluded that the level of democratic practice of the teachers is favorable.